Language structure reflects biases in pattern learning across domains and modalities - Culbertson, Jennifer; Compostella, Arianna; Kirby, Simon (Quarterly journal of experimental psychology (2006), 2025)
A central goal for psychological science is the explanation of variation in human behaviour. In the domain of language, patterns of cross-linguistic variation have been extensively documented, but there has been vigorous debate over how to explain them. A particularly contentious question is whether constraints on linguistic variation are driven by properties of the human mind that are specific to language or domain-general. In this paper, we present four pattern-learning experiments ( = 306 English- and Italian-speaking adults) across domains (linguistic and nonlinguistic) and modalities (visual, auditory, and tactile) to show that the patterns that are more easily learned are precisely the ones that are found most frequently across languages. This supports a domain-general, cognitive explanation for cross-linguistic variation. However, we suggest that the general/specific dichotomy is ultimately misleading because language structure arises when domain- and modality-general biases meet domain-specific representations.